(untitled) (Journal of the Bangladesh Agricultural University, 2019)
A study was conducted from July 2013 to June 2016 on production rate, quality, and color of pearl, cultured at Trishal, Fulbaria and BFRI (Bangladesh Fisheries Research Institute) of Mymensingh region. Freshwater pearl producing mussel, Lamellidens marginalis was used in this experiment. Eighty mussels per decimal were stocked in integration with fish culture. Three ponds from three locations were used. The area of each pond was 40 decimal having water depth of 1.5m in Trishal, Fulbaria and BFRI respectively. Water temperature, pH, Ammonia, Dissolve oxygen, Alkalinity, Ca2+ and Phytoplankton (× 103) ranged from 25.37-28.730C, 6.2-7.92, 0.02-0.3mg/l, 5.09-6.08mg/l, 100.17-191.50, 15.31-25.87and 48.99-63.45, respectively. Survival rate of the operated mussels were 30.62%, 34.62% and 40.25%, respectively. After 3 years of rearing, 53%, 76% and 93% pearls containing mussels were harvested from Trishal, Fulbaria and BFRI respectively. After final harvesting total pearl production, its quality and color were observed and found better at the location of BFRI, followed by Trishal and Fulbaria. Research study concluded that, the quality of pearl depends on intensive care, proper management, suitable water quality parameter, sunlight penetration, food availability and soil quality of the culture pond. J Bangladesh Agril Univ 17(3): 424–429, 2019